Opportunities for new physics searches with heavy ions at colliders. (1st May 2023) - d'Enterria, David; Drewes, Marco; Giammanco, Andrea; Hajer, Jan; Bratkovskaya, Elena; Bruce, Roderik; Burmasov, Nazar; Dyndal, Mateusz; Gould, Oliver; Grabowska-Bold, Iwona; Gumberidze, Malgorzata; Gunji, Taku; et al.
Abstract: Opportunities for searches for phenomena beyond the Standard Model (BSM) using heavy-ions beams at high energies are outlined. Different BSM searches proposed in the last years in collisions of heavy ions, mostly at the Large Hadron Collider, are summarized. A few concrete selected cases are reviewed including searches for axion-like particles, anomalous τ electromagnetic moments, magnetic monopoles, and dark photons. Expectations for the achievable sensitivities of these searches in the coming years are given. Studies of CP violation in hot and dense QCD matter and connections to ultrahigh-energy cosmic rays physics are also mentioned.